2019
DOI: 10.1016/j.envpol.2019.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Environmental perfluoroalkyl acid exposures are associated with liver disease characterized by apoptosis and altered serum adipocytokines

Abstract: Exposures to perfluoroalkyl substances (PFAS) including perfluoroalkyl acids (PFAAs) are associated with increased liver enzymes in cohort studies including the C8 Health Study. In animal models, PFAAs disrupt hepatic lipid metabolism and induce apoptosis to cause nonalcoholic fatty liver disease (NAFLD). PFAAs are immunotoxic and inhibit pro-inflammatory cytokine release from stimulated leukocytes in vitro. This cross-sectional study tests the hypothesis that environmental PFAAs are associated with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 57 publications
6
82
0
Order By: Relevance
“…(Mora et al 2018) In studies examining other markers of liver injury, positive associations were reported between PFAS (including PFOA and PFHxS) and cytokeratin 18, a marker for liver apoptosis, but inverse relationships were reported between PFAS and serum pro-inflammatory cytokines in adults. (Bassler et al 2019)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Mora et al 2018) In studies examining other markers of liver injury, positive associations were reported between PFAS (including PFOA and PFHxS) and cytokeratin 18, a marker for liver apoptosis, but inverse relationships were reported between PFAS and serum pro-inflammatory cytokines in adults. (Bassler et al 2019)…”
Section: Discussionmentioning
confidence: 99%
“…(Fromme et al 2009) Animal studies show that PFAS exposure to rodents causes liver enlargement, hepatocellular hypertrophy, elevated liver enzymes, and hepatic steatosis. (Das et al 2017; Martin et al 2007; Son et al 2008; Wan et al 2012; Wang, L. et al 2013; Wu et al 2017; Wu et al 2018) Recent cross-sectional studies in adults showed that elevated serum concentrations of PFOA were associated with increased levels of alanine aminotransferase (ALT), a surrogate marker for NAFLD (Gleason et al 2015; Lin et al 2010), and cytokeratin 18, a marker for liver apoptosis (Bassler et al 2019) Children are reported to have increased burden of PFAS exposure relative to body size (Morck et al 2015); however, there are few studies investigating PFAS hepatotoxicity in children. The only study published to date found negative associations of prenatal and childhood plasma PFAS concentrations with ALT levels at age 8 years.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41] Studies also indicate that exposure is associated with metabolic effects, ulcerative colitis and adverse effects on liver and kidney function. [42][43][44][45] Several firefighter biomonitoring studies measured PFAS levels and found higher levels among firefighters compared to the general population. 25,27,28 These studies, however, included few or no women.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, several studies have shown that elevated levels of PFASs are linked to altered levels of markers of liver function, such as ALP, ALT, AST, and GGT. 42 43 44 …”
Section: Pfas and Liver Fatmentioning
confidence: 99%
“…In two hundred individuals in the C8 Health Study, several of the PFASs—PFHxS, PFOA, PFNA—were related to circulating levels of cytokeratin 18 M30, a marker of liver cell apoptosis. 42 However, we are still lacking studies clearly showing that background exposure to PFAS in the general population will induce NAFLD.…”
Section: Pfas and Liver Fatmentioning
confidence: 99%